The Korean species of the genus Thinodromus Kraatz (Coleoptera: Staphylinidae: Oxytelinae) - Lee, Seung-Il; Ahn, Kee-Jeong (Zootaxa, 2007)
A taxonomic study of the genus Thinodromus Kraatz in Korea is presented. Four species are recognized, two of which are new to Korea: Thinodromus (T.) bernhaueri (Klima) and T. (T.) deceptor (Sharp). Males of Thinodromus (T.) deceptor (Sharp) are described for the first time. A key, illustrations of the habitus, and line drawings of diagnostic characters are provided.